2021
DOI: 10.1021/acs.inorgchem.0c03306
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative B–H and Si–H Bond Activations by κ2-N,S-Chelated Ruthenium Borate Complexes

Abstract: Cooperative E–H (E = B, Si) bond activations employing κ2-N,S-chelated ruthenium borate species, [PPh3{κ2-N,S-(NS2C7H4)}­Ru­{κ3-H,S,S′-H2B­(NC7H4S2)2}], (1) are established. Treatment of 1 with BH3·SMe2 yielded the six-membered ruthenaheterocycle [PPh3{κ2-S,H-(BH3NS2C7H4)}­Ru­{κ3-H,S,S’-H2B­(C7H4NS2)2}] (2) formed by a hemilabile ring opening of a Ru–N bond and capturing of a BH3 unit coordinated in an “end-on” fashion. On the other hand, the bulky borane H2BMes shows different reactivity with 1 that led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…Interestingly, not many examples are known where the addition of H 2 BMes occurred in a κ 2 -coordination fashion into the polar M–L bonds. 7 b ,17,38 Some of the dihydroborate species, for example, [Cp*Ru(κ 3 - P , H , H -( i Pr)P(C 9 H 6 O–H 2 BMes)] 38 and [M{κ 3 - N , H , H -Xyl( N )P(OH 2 BMes)(OEt) 2 }(η 4 -COD)] (M = Rh and Ir), 7 b have been isolated from the insertion of H 2 BMes into the corresponding M–O bonds. The first bis(σ-borane) species, [Ru(PCy 3 ) 2 (H) 2 (η 2 :η 2 -BH 2 Mes)], was reported by Sabo-Etienne and Alcaraz, isolated from the reaction of H 2 BMes and [RuH 2 (PCy 3 ) 2 (η 2 -H 2 ) 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, not many examples are known where the addition of H 2 BMes occurred in a κ 2 -coordination fashion into the polar M–L bonds. 7 b ,17,38 Some of the dihydroborate species, for example, [Cp*Ru(κ 3 - P , H , H -( i Pr)P(C 9 H 6 O–H 2 BMes)] 38 and [M{κ 3 - N , H , H -Xyl( N )P(OH 2 BMes)(OEt) 2 }(η 4 -COD)] (M = Rh and Ir), 7 b have been isolated from the insertion of H 2 BMes into the corresponding M–O bonds. The first bis(σ-borane) species, [Ru(PCy 3 ) 2 (H) 2 (η 2 :η 2 -BH 2 Mes)], was reported by Sabo-Etienne and Alcaraz, isolated from the reaction of H 2 BMes and [RuH 2 (PCy 3 ) 2 (η 2 -H 2 ) 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 cooperative Si-H and B-H bond activations by κ 2 -N,S-chelated borate complex, trans-mer-1b that led to the formation of sixmembered ruthenahetero-cycles through hemilabile ringopening of Ru−N bonds. 17 While working on κ 2 -N,S-chelated species trans-mer-1a-b, we have observed that aerial oxidation of these Ru(II) complexes unusually generate redox-active Ru(III) species, mer-2a-b that contain dual reactive sites. As a result, we have explored the reactivity of these redox-active Ru(III) species with different types of boranes that demonstrate the synergetic effect of metal and redox active ligands for the activation of boranes.…”
Section: Introductionmentioning
confidence: 97%
“…[102] This synthetic approach has been capitalised to generate TM borate complexes by several groups including those of stradiotto, [105] Oestreich, [106] Wang, [107] Gessner [108] and us. [109][110] While exploring the reactivity of k 2 -N,S-chelated TM complexes towards various boranes, [109] [111] The presence of BÀ H terminal proton in 25 was indicated by the broad signals at δ = 8.03 and 3.98 ppm in the 11 B{ 1 H} and 1 H NMR spectra, respectively. The molecular structure of 25 displayed a k 2 -S,S-chelated ring in which the sulfur is coordinated to rhodium and nitrogen is coordinated to boron (Figure 12).…”
Section: K 2 -Coordinationmentioning
confidence: 99%
“…SMe 2 led to the formation of hydroborate species [PPh 3 {k 2 -S,H-(BH 3 NS 2 C 7 H 4 )}Ru {k 3 -H,S,S-H 2 B(C 7 H 4 NS 2 ) 2 }] in which both thek 2 -S,H and k 3 -H,S,S coordination modes of the borate ligand are present. [109] Therefore, the insertion of boranes into a hemilabile ligand backbone of a TM complex is an alternative to the utilisation of the borane proligands to generate borate complexes.…”
Section: K 3 -Coordinationmentioning
confidence: 99%
“…Coordination of borane and silane molecules to a transition-metal center is a fundamental step in achieving E–H (E = B or Si) σ-bond activation, leading principally to the hydrido boryl or silyl complexes. These organometallic species are envisioned as key intermediates in the catalytic introduction of boron or silicon moieties into unsaturated hydrocarbons. The interest in iron borane and iron silane chemistry arises from the research priority of searching for low-cost alternatives to the conventionally used noble metal-based catalysts. …”
Section: Introductionmentioning
confidence: 99%